Connecting the Drops: Observing Collective Flow Behavior in Emulsions - Dijksman, Joshua A. (Frontiers in Physics, 2019)
Thoroughly mixing immiscible fluids creates droplets of one phase dispersed in a continuum of the other phase. In such emulsions, the individual droplets have rather mundane mechanical behavior. However, densely confining these suspended droplets generates a packing of particles with a spectacular diversity of mechanical behavior whose origins we are only beginning to understand. This mini review serves to survey a non-exhaustive range of experimental dense slow flow emulsion work. To embed these works in the context of the flow behavior of other structured fluids, we also discuss briefly the related nonlocal flow modeling attempts as one of the approaches that has been used successfully in describing emulsion flow properties and other materials.